ISBAT NIKAH BAGI PASANGAN CERAI MATI PADA PENGADILAN AGAMA KELAS 1A WATAMPONE PERSEPEKTIF HUKUM ISLAM - Andi Syamsulbahri (IAIN BONE, 2022)
AbstractThis article discusses the isbat nikah case for married couples who have died, by knowing the views of Islamic law on the isbat nikah case. The qualitative type, with the case study method, which is carried out in detail, is intensive on the phenomenon. The results showed that the judge granted the application for isbat nikah with the consideration that the marriage was carried out in accordance with Islamic law and occurred before the enactment of Law Number 1 of 1974, as one of the basis for the declarative dictum decision. Meanwhile, the view of Islamic law on the isbat nikah of a husband and wife who have been divorced, it is considered okay to submit an application, but the couple will not have a marriage certificate because it is not recorded at the Religious Affairs office for the reasons contained in Article 7, provided that during the marriage carried out in accordance with Islamic law.Keywords: Death divorce; Islamic law; Isbat Nikah